Performance of graduates ones of the Faculty of Dentistry of Universidad Nacional Mayor de San Marcos in Dentistry Institutions - Arroyo Pérez, Carlos (2011)
Professional performance of graduates in dentistry, is not only exclusive in the area of oral diseases treatment, but, as a bearer of professional identity, he leads the process of societal transformation and the development of the profession, exercising positions in university educational institutions, in scientific and professional dental institutions unions. Models that accredit university carriers recognize the graduate bachelor and his social performance as an important factor for the issue of quality judgments of the carrier in mention. The aim of this paper is to demonstrate the presence of graduates of dentistry from Universidad Nacional Mayor de San Marcos in professional institutions through time, and motivate members of San Marcos dental community about the role to play in the development of Peruvian Dentistry, analyzing the role of San Marcos dental graduates in leading scientific institutions of our country. The study is descriptive, transversal and exploratory. Information was collected from the archives of institutions through a card. The sampling was not ramdom. The results confirm that graduates in the last 20 years have been leading various institutions with a 55% stake in national dental institutions.